RESOLUTION OF CASES OF ALLEGED MALPRACTICE OF BIDAN IN SUPPORTING BIRTH IN HOSPITALS BY PENAL MEDIATION (Case study of alleged midwife malpractice in a Cirebon Regency hospital) - Dino Ubassandrio; Raja Ath-Thuur Rabbani; Wahyudin Wahyudin; Sri Primawati Indraswari; Harmono Harmono (Al-Makki Publisher, 2024)
Malpractice is an error of medical personnel in carrying out their profession that is not in accordance with professional standards and standard operating procedures, resulting in the patient receiving serious injuries, disabilities, and even death. This study aims to analyze the factors that cause the alleged malpractice of midwives in assisting childbirth and the settlement of cases of alleged malpractice with penal mediation. In this study, the method used is a normative juridical approach that involves analyzing the applicable laws related to malpractice cases by midwives as well as reviewing recent cases, with the use of secondary data collection techniques focused on literature review. The results of this study conclude that the main factor in the occurrence of malpractice in midwives is the existence of errors in the form of both negligence and culpa caused by carelessness. The settlement of alleged malpractice cases with penal mediation is a settlement of cases outside the court by bringing together the parties involved, one of the alternative solutions is Penal Mediation. These findings can provide a deeper understanding of the application of responsibility in the context of alleged malpractice by midwives and can contribute to the improvement of legal norms that are more effective in dealing with these problems. The implications of the results of this study are expected to serve as a guide for the authorities, legal practitioners, and the public in facing and understanding the challenges associated with alleged malpractice cases involving midwives.